2020
DOI: 10.3991/ijet.v15i11.13267
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning Technology: An Example in Programming Microcontrollers

Abstract: This article presents the technology of the organization of project-based learning in programming microcontrollers at the faculty of information technology (L.N. Gumilyov Eurasian National University). Based on the analysis of scientific-methodical and normative documents, scientific articles was developed a structural model of the organization of the project-based learning in programming microcontrollers. All the processes of the project development life cycle and the role of each member of the project team w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…However, low-performing students in this study had a positive attitude toward collaboration. erefore, getting students to write code together in pairs or small groups can enhance students' programming performance and confidence [52][53][54]. Pair programming produces more rapid and effective solutions than solo programming [75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, low-performing students in this study had a positive attitude toward collaboration. erefore, getting students to write code together in pairs or small groups can enhance students' programming performance and confidence [52][53][54]. Pair programming produces more rapid and effective solutions than solo programming [75].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to motivating the students, instructors should provide novices with fundamental skills and simple problem solving before starting the course so that novices have the background needed to understand basic programming. Previous studies have suggested various teaching methods: live coding, gamification, team based-learning, interactive computer tutors, mentor support, peer instruction, and pair programming [47][48][49][50][51][52][53][54]. However, some of these teaching methods do not always succeed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, instead of sorting network, the instructor introduced the sorting algorithm with bubble sort activities, and also controlled the activities duration within 20 min according to the time limitation of the class. The content are required to be taught with Python in China's high school according to the Information Technology Curricula for China's high schools (MOE, 2020). During the instruction and learning processes, in the IDL class, learners received the instructor-directed lecturing with oral presentations to learn programming concepts and algorithms (see Fig.…”
Section: Research Context Participants and Instructional Proceduresmentioning
confidence: 99%
“…For example, Aizpun et al (2015) collaborated with Adidas and asked the students to redesign an existing product, allowing them to increase their motivation while working with them. On the other hand, Nurbekova et al (2020) placed students of a microcontrollers programming course in groups with general topics to work on, giving them total freedom to organise themselves and complete the tasks required for their final project. Studies on accounting application in real life (Carrasco et al, 2018), project-based learning mixing professional English teaching and music (Borisova & Letkina, 2019) and the use of the methodology to compare its differences with the traditional way of teaching in universities (Bilgin et al, 2015) are successful examples of how projectbased learning can be applied in multiple fields of study.…”
Section: Project-based Learningmentioning
confidence: 99%